Influence of Nitrogen, Potassium and Phosphorus Fertilizers with Foliar Application of Micronutrient of Iron, Zinc and Manganese on Bulb Characteristics of Single Flower Tuberose Plants (Polianthes Tuberosa, L.) - Sabah Abdalghani; Zakia Fadhil; Muneerah Rizq; Fatan Muhammed (AlQalam Journal of Medical and Applied Sciences, 2024)
The global market for flowers and ornamental plants is expected to expand at a rate of approximately 6.3% over the next five years, reaching an estimated value of 57.4 billion USD by 2024. Tuberose (Polianthes tuberosa L.), a summer flower cultivated by small-scale growers primarily for export. The study was aimed to cultivate tuberose plants in Al-Jabal Al-Khader region, introducing them as a new cut flower crop, as a source for tuberose, and leveraging their economic potential. A field experiment was conducted over two summer growing seasons to investigate the impact of different levels of compound fertilizer (nitrogen, phosphorus and potassium, NPK 4:4:4) in application rates (0, 500, 1000, and 1500 kg.ha-1) and foliar sprays of micronutrients iron (Fe), zinc (Zn), manganese (Mn), and a )mixture of these three elements) on tuberose bulbs. The experimental design was a completely randomized block design split-plot with three replications. The NPK fertilizer levels were randomly assigned to the main plots, while the micronutrient treatments were allocated to the subplots. The study found that varying rates of NPK fertilization did not significantly affect the number of bulbs per plant over the two growing seasons. In contrast, the application of micronutrient foliar sprays had a notable impact, with the mixture of Fe, Zn, and Mn yielding the highest significant increase in bulb number per plant in both seasons. It is recommended to apply a mixture of the three micronutrients (Fe, Zn, and Mn) as fertilizer to produce high-quality Tuberose plants for various decorative purposes in landscaping. من المتوقع أن يتوسع السوق العالمي للزهور والنباتات الزينة بمعدل 6.3٪ تقريبًا على مدى السنوات الخمس المقبلة، ليصل إلى قيمة تقديرية تبلغ 57.4 مليار دولار أمريكي بحلول عام 2024. مسك الروم (Polianthes tuberosa L.)، زهرة صيفية يزرعها مزارعون صغار في المقام الأول للتصدير. هدفت الدراسة إلى زراعة نباتات مسك الروم في منطقة الجبل الأخضر، وتقديمها كمحصول جديد من الزهور المقطوفة، كمصدر لمسك الروم، والاستفادة من إمكاناتها الاقتصادية. أجريت تجربة ميدانية على مدار موسمين صيفيين للنمو للتحقيق في تأثير مستويات مختلفة من الأسمدة المركبة (النيتروجين والفوسفور والبوتاسيوم، NPK 4:4:4) في معدلات التطبيق (0، 500، 1000، و 1500 كجم. هكتار -1) والرش الورقي للعناصر الغذائية الدقيقة الحديد (Fe) والزنك (Zn) والمنجنيز (Mn) و (مزيج من هذه العناصر الثلاثة) على بصيلات مسك الروم. كان التصميم التجريبي عبارة عن تصميم كتلة عشوائية كاملة مع تقسيم القطع بثلاثة مكررات. تم تعيين مستويات سماد NPK عشوائيًا للقطع الرئيسية، في حين تم تخصيص معالجات العناصر الغذائية الدقيقة للقطع الفرعية. وجدت الدراسة أن المعدلات المتفاوتة من تسميد NPK لم تؤثر بشكل كبير على عدد البصيلات لكل نبات خلال موسمي النمو. في المقابل، كان لتطبيق الرش الورقي للعناصر الغذائية الدقيقة تأثير ملحوظ، حيث أعطى خليط الحديد والزنك والمنجنيز أعلى زيادة كبيرة في عدد البصيلات لكل نبات في كلا الموسمين. يوصى باستخدام خليط من العناصر الغذائية الدقيقة الثلاثة (الحديد والزنك والمنجنيز) كسماد لإنتاج نباتات مسك الروم عالية الجودة لأغراض الزينة المختلفة في المناظر الطبيعية